Pengaruh Kualitas Pelayanan, Citra Merek dan Persepsi Harga Terhadap Kepuasan Pelanggan Pada Layanan Go-ride - Sumarah Budi Santoso; Rayhan Gunaningrat; Esti Dwi Rahmawati (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
The development of information technology, in terms of the internet is increasing and increasingly making people feel more comfortable to carry out various activities. The transportation business is also not spared from advances in internet technology. Online motorcycle taxis and taxis are a business opportunity that takes advantage of the development of internet technology. Traditional motorcycle taxis and taxis can only be found at the base or contacted by telephone. However, the current access can be accessed using an Android-based application. The emergence of transportation businesses such as Go-jek, Grab, Maxim and Indriver is proof that information technology has also penetrated into public transportation. The type of research used is quantitative research using multiple linear regression analysis techniques. The population in this study were 100 Go-ride service users in Solo Raya. The data collection technique used is questionnaire using the Linkert scale. The conclusions of this study are (1) There is a significant influence between service quality on customer satisfaction, (2) There is no significant influence between brand image on customer satisfaction, (3) There is a significant influence between price perceptions on customer satisfaction, (4) Simultaneously service quality, brand image and price perceptions have an effect on customer satisfaction.